2018
DOI: 10.3920/wmj2018.2314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mycotoxin contamination in maize and wheat stored in silos using two sampling processes

Abstract: Mycotoxin contamination of stored cereals often occurs in a highly heterogeneous manner, necessitating the use of representative sampling to minimise analytical errors. The objective of this study was to compare mycotoxin analysis in stored maize and wheat using two sampling processes. Samples were obtained from four maize silos and two wheat silos. A pneumatic probe was introduced in the centre and at the four central points of each quadrant, from the top to the bottom of the silo (12 m). For sampling process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An additional study found that FB1 levels ranged from 0.5 to 3.9 μg/kg of wheat and between 0.6 and 2.3 μg/kg of flour (Birck et al, 2003). There were 74% (24.91%) of wheat samples contaminated with DON from the southern region, and levels of toxins ranged from 603.2 to 850.4 μg/kg (Mallmann et al, 2003). Sulyok et al (2006) determined the detection limits of DON in wheat samples which ranged from 0.03 to 220 μg/kg.…”
Section: Wheat (Triticum Aesticum L)mentioning
confidence: 99%
“…An additional study found that FB1 levels ranged from 0.5 to 3.9 μg/kg of wheat and between 0.6 and 2.3 μg/kg of flour (Birck et al, 2003). There were 74% (24.91%) of wheat samples contaminated with DON from the southern region, and levels of toxins ranged from 603.2 to 850.4 μg/kg (Mallmann et al, 2003). Sulyok et al (2006) determined the detection limits of DON in wheat samples which ranged from 0.03 to 220 μg/kg.…”
Section: Wheat (Triticum Aesticum L)mentioning
confidence: 99%
“…e use of vertical silos for cereal storage, sometimes equipped with temperature control and aeration, is a common practice for preserving grain quality and safety. However, even with the strictest control practices, stored cereals can present mycotoxin contamination [12]. In rice, there have been reports of the so-called eld mycotoxins such as those produced by Fusarium due to accumulation at significant levels before drying and storage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of grains and seeds with mycotoxins occurs widely and affects cereals of economic and food importance such as wheat, which is a source of raw material for the production of various foodstuffs, fundamental in human diet. Triticum aestivum, known as common wheat, is the most widely planted species on the planet and the most common grain used for bread-making (Mallmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%